The Oxford history of the laws of England : Volume XI : 1820-1914, English legal system - Cornish, W. R. (William Rodolph), 1937- (Oxford : Oxford University Press, 2010)
'The Oxford History of the Laws of England: Volume XI 1820-1914 English Legal System' is one of three volumes devoted to that period of relative peace across Europe running from the defeat of Napoleon to the terrible war against the two Kaisers.
Includes bibliographical references and index.
Also available as part of the print set.
Description based on print version record.
Keywords: Law -- England -- History -- 19th century; Law -- England -- History -- 20th century